TGIF1 functions as a tumor suppressor in pancreatic ductal adenocarcinoma. (31st May 2019) - Parajuli, Parash; Singh, Purba; Wang, Zhe; Li, Lianna; Eragamreddi, Sailaja; Ozkan, Seval; Ferrigno, Olivier; Prunier, Celine; Razzaque, Mohammed S; Xu, Keli; Atfi, Azeddine
Abstract: A prominent function of TGIF1 is suppression of transforming growth factor beta (TGF‐β) signaling, whose inactivation is deemed instrumental to the progression of pancreatic ductal adenocarcinoma (PDAC), as exemplified by the frequent loss of the tumor suppressor gene SMAD4 in this malignancy. Surprisingly, we found that genetic inactivation of Tgif1 in the context of oncogenic Kras, Kras G12D, culminated in the development of highly aggressive and metastatic PDAC despite de‐repressing TGF‐β signaling. Mechanistic experiments show that TGIF1 associates with Twist1 and inhibits Twist1 expression and activity, and this function is suppressed in the vast majority of human PDACs by Kras G12D /MAPK‐mediated TGIF1 phosphorylation. Ablating Twist1 in Kras G12D ;Tgif1 KO mice completely blunted PDAC formation, providing the proof‐of‐principle that TGIF1 restrains Kras G12D ‐driven PDAC through its ability to antagonize Twist1. Collectively, these findings pinpoint TGIF1 as a potential tumor suppressor in PDAC and further suggest that sustained activation of TGF‐β signaling might act to accelerate PDAC progression rather than to suppress its initiation. Synopsis: Pathogenesis of pancreatic ductal cancer (PDAC) is driven by the recurrent oncogenic Kras G12D mutation. Here, genetic findings uncover the homeodomain protein TG‐interacting factor 1 (TGIF1) to be inactivated by phosphorylation orchestrated by constitutive Kras, providing new insights into biphasic roles of TGF‐β signaling during PDAD initiation and progression. A video of this synopsis is available online at http://www.embopress.org/video_EMBOJ_2018_101067 . TGIF1 is dispensable for normal pancreatic development. Pancreas‐specific Tgif1 inactivation accelerates Kras G12D ‐driven tumorigenesis and metastasis in mice. TGIF1 restricts PDAC through repression of Twist1 expression and activity. Phosphorylation of TGIF1 by constitutive Kras G12D /MAPK signaling disrupts its tumor suppressor function in human PDAC. Abstract : The TGF‐β regulator TGIF1 exerts unanticipated roles in antagonizing the pro‐malignant transcription factor Twist1 in pancreatic cancer.